Multipartner Symbiosis across Biological Domains: Looking at the Eukaryotic Associations from a Microbial Perspective - Marta Turon (American Society for Microbiology, 2019)
ABSTRACT Sponges establish tight associations with both micro- and macroorganisms. However, while studies on sponge microbiomes are numerous, nothing is currently known about the microbiomes of sponge-associated polychaetes and their relationships with those of their host sponges. We analyzed the bacterial communities of symbiotic polychaetes (Haplosyllis spp.) and their host sponges (Clathria reinwardti, Amphimedon paraviridis, Neofibularia hartmani, and Aaptos suberitoides) to assess the influence of the sponges on the polychaete microbiomes. We identified both eukaryote partners by molecular (16S and COI genes) and morphological features, and we identified their microbial communities by high-throughput sequencing of the 16S rRNA gene (V4 region). We unravel the existence of six Haplosyllis species (five likely undescribed) associated at very high densities with the study sponge species in Nha Trang Bay (central Vietnam). A single polychaete species inhabited A. paraviridis and was different from the single species that inhabited A. suberitoides. Conversely, two different polychaete species were found in C. reinwardti and N. hartmani, depending on the two host locations. Regardless of the host sponge, polychaete microbiomes were species specific, which is a widespread feature in marine invertebrates. More than half of the polychaete bacteria were also found in the host sponge microbiome but at contrasting abundances. Thus, the associated polychaetes seemed to be able to select, incorporate, and enrich part of the sponge microbiome, a selection that appears to be polychaete species specific. Moreover, the bacterial diversity is similar in both eukaryotic partners, which additionally confirms the influence of food (host sponge) on the structure of the polychaete microbiome. IMPORTANCE The symbiotic lifestyle represents a fundamental cryptic contribution to the diversity of marine ecosystems. Sponges are ideal targets to improve understanding the symbiotic relationships from evolutionary and ecological points of view, because they are the most ancient metazoans on earth, are ubiquitous in the marine benthos, and establish complex symbiosis with both prokaryotes and animals, which in turn also harbor their own bacterial communities. Here, we study the microbiomes of sponge-polychaete associations and confirm that polychaetes feed on their host sponges. The study worms select and enrich part of the sponge microbiome to shape their own species-specific bacterial communities. Moreover, worm microbiome diversity runs parallel to that of its food host sponge. Considering our results on symbiotic polychaetes and previous studies on fishes and mammals, diet appears to be an important source of bacteria for animals to shape their species-specific microbiomes.